Effect of a multifaceted social franchising model on quality and coverage of maternal, newborn, and reproductive health-care services in Uttar Pradesh, India: a quasi-experimental study - Sarah Tougher, MSc; Varun Dutt, PGDip; Shreya Pereira, MSc; Kaveri Haldar, MPP; Vasudha Shukla, PhD; Kultar Singh, PGDip; Paresh Kumar, PGDip; Prof Catherine Goodman, PhD; Timothy Powell-Jackson, PhD (Elsevier, 2018)
Background: How to harness the private sector to improve population health in low-income and middle-income countries is heavily debated and one prominent strategy is social franchising. We aimed to evaluate whether the Matrika social franchising model-a multifaceted intervention that established a network of private providers and strengthened the skills of both public and private sector clinicians-could improve the quality and coverage of health services along the continuum of care for maternal, newborn, and reproductive health. Methods: We did a quasi-experimental study, which combined matching with difference-in-differences methods. We matched 60 intervention clusters (wards or villages) with a social franchisee to 120 comparison clusters in six districts of Uttar Pradesh, India. The intervention was implemented by two not-for-profit organisations from September, 2013, to May, 2016. We did two rounds (January, 2015, and May, 2016) of a household survey for women who had given birth up to 2 years previously. The primary outcome was the proportion of women who gave birth in a health-care facility. An additional 56 prespecified outcomes measured maternal health-care use, content of care, patient experience, and other dimensions of care. We organised conceptually similar outcomes into 14 families to create summary indices. We used multivariate difference-in-differences methods for the analyses and accounted for multiple inference. Findings: The introduction of Matrika was not significantly associated with the change in facility births (4 percentage points, 95% CI −1 to 9; p=0·100). Effects for any of the other individual outcomes or for any of the 14 summary indices were not significant. Evidence was weak for an increase of 0·13 SD (95% CI 0·00 to 0·27; p=0·053) in recommended delivery care practices. Interpretation: The Matrika social franchise model was not effective in improving the quality and coverage of maternal health services at the population level. Several key reasons identified for the absence of an effect potentially provide generalisable lessons for social franchising programmes elsewhere. Funding: Merck Sharp and Dohme Limited.